Kaidah Kesahihan Hadis dan Penerapannya dalam Penelitian Hadis - Irfan, Muhammad (Lembaga Yasin AlSys, 2022)
Hadith is one source of Islamic teachings. However, not all quality hadiths are accepted. So we need a method to find out the hadith that can be used as a basis in the teachings of Islam. In this article, the researcher wants to explain the validity of hadith and how to apply it in research on the quality of hadith, both in terms of the sanad and the matan, because the rules of validity of hadith are a reference for determining the quality of a hadith. This research is library research. From various literatures it is found that to reach a conclusion the status of a hadith must go through the stages of I'tibar hadith and sanad criticism, then criticism of matan if the sanad meets the requirements.